Comparative Forensic Examination of Signatures Executed on Paper and Stylus-Based Digital Devices (Journal of Forensic Medicine & Toxicology, 2026)
Handwritten signatures serve as a primary means of authentication in legal, financial, and administrative contexts. With the increasing use of stylus based digital devices, signatures are frequently executed on electronic platforms, raising questions regarding their forensic comparability with conventional pen & paper signatures. Handwriting represents a complex motor skill involving coordinated neuromuscular activity, and variations may arise due to changes in writing conditions. The present study examines the similarities and differences between signatures written on paper and those executed on a digital tablet (iPad) using a stylus. A total of 100 participants provided paired signature samples under both conditions, and seventeen handwriting characteristics were evaluated using a four-point ordinal scale. The results indi cate that most characteristics exhibit either no variation or slight variation across writing media, with moderate variation observed only in a limited number of execution related features and no instances of extreme variation. Structural characteristics, including letter formation, spacing, and overall signature configuration, remained largely consistent, while minor differences were observed in dynamic features such as pen movement, line quality, and writing speed. The find ings suggest that variations introduced by digital writing conditions fall within the range of natural variation and do not significantly alter fundamental handwriting characteristics, thereby supporting the reliability of forensic comparison of electronically executed signatures when medium related variations are considered appropriately.
Keywords: Questioned document examination, electronically formed signatures, handwriting comparison, stylus signa tures, questioned documents